An approach to the scope of the Inter-American Court of Human Rights in the fight for Afro-descendant territorial rights - Agudelo, Carlos (2023)
One of the tools used by Afro-descendant peoples in Latin America and the Caribbean in their fight for territorial rights has been resorting to the courts. This article focuses on the specific role played by the Inter-American Court of Human Rights in relation to the territorial claims of Afro-descendant peoples. It is an ongoing investigation on the use of justice as a tool in the struggle of Afro-descendant peoples in Latin America and the Caribbean, which is currently in a phase of data systematization (judgments, jurisprudence, related studies) with gradual elements of analysis that should be enriched. Hence, the extensive inclusion of documentation from the Inter-American Court. Initially, we present a panoramic view of the situation of Afro-descendant territories. Then, we provide a general framework of the Inter-American Human Rights System and its history of involvement in cases related to ethnic groups and their territories. Next, a chronological systematization is presented of the cases that have reached the Inter-American Court directly related to the demands of Afro-descendant groups and territorial claims. Based on documents from the Court that are part of the respective processes, we analyze elements of the arguments and sentences that provide a general idea to understand the scope of these cases. Finally, we offer some initial reflections on the possibilities and limitations presented by the sentences of the Inter-American Court.